President’s Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2019)
The theme for Perioperative Nurses Week this year was Perioperative Nursing: Unified Voice for Excellence in Patient Safety. The poster showed a patient surrounded by the whole Perioperative team. When we, as Perioperative Nurses, think of teamwork and collaboration that is what usually comes to mind – collaborating with an entire team of health care professionals in order to provide high-quality, safe, surgical care. After attending a recent event at our local hospital I began, however, to think about a unified voice as being more than just the team within the hospital walls.